2018
DOI: 10.30983/educative.v3i2.544
|View full text |Cite
|
Sign up to set email alerts
|

Conscientiousness and Emotional Stability on Students’ Speaking Ability Through Flipped Classroom

Abstract: <p class="abstrak">The purpose of this study was to analyze the differences of students’ speaking ability in the Flipped Classroom model by using 1) audiovisual media, 2) printed media, 3) online learning WhatsApp and Massive Open Online English Course (MOOEC) in terms of students’ personality of <strong>c</strong>onscientiousness and emotional stability. An experimental research method was used in this study where the data taken from 56 students who enroll class eleventh at Senior High Schoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This study is consistent with previous findings that reported a positive interaction between the online-based flipped classroom method with different media on students' awareness and emotional stability on speaking skills (Alsowat, 2016;Reflianto, 2018). Likewise, it revealed that the flipped classroom online method with student engagement also interacted and affected students' English learning outcomes (Zen et al, 2019).…”
Section: Interaction Effect Between Online-based Flipped Classroom Le...supporting
confidence: 91%
“…This study is consistent with previous findings that reported a positive interaction between the online-based flipped classroom method with different media on students' awareness and emotional stability on speaking skills (Alsowat, 2016;Reflianto, 2018). Likewise, it revealed that the flipped classroom online method with student engagement also interacted and affected students' English learning outcomes (Zen et al, 2019).…”
Section: Interaction Effect Between Online-based Flipped Classroom Le...supporting
confidence: 91%
“…Teacher has to understand and consider it in the classroom. Consciousness and personalities like emotional stability play an important role in the achievement of students' speaking ability (Reflianto, Farida Ariani;2018). Students will speak well if they have good emotional stability as their personalities.…”
Section: Introductionmentioning
confidence: 99%